Penerapan Prinsip Kehati-hatian dalam Penyaluran Pembiayaan dan Kredit pada Lembaga Keuangan Mikro (Studi Multi Situs pada BMT Hasanah Mlarak dan BRI Unit Mlarak, Ponorogo) - Rahma Yudii Astuti (Al Tijarah, 2016)
Microfinance institutions like the company has a motive to obtain a return (net income) are always faced with the risk, which is known as credit risk. Risks that may occur can cause great harm to financial institutions if it can not be detected and managed by microfinance semestinya.Lembaga always required to be more sensitive in detecting things that could trigger a rise in the level of non performing loan. The credit risk is the risk of potential losses resulting from the non settlement of bank loans back to the bank’s borrowers and counterparties lainnya.Penelitian a field research (field research) that are normative. Data were collected through observation, documentation, and interviews, while the type of data used are primary data and secondary data. Microfinance institutions that implement the precautionary principle in the procedures of channeling financing and credit based on standard guidelines or SOP, focus on monitoring PPAP by age collectibility of the loans/loans, to restrict credit expansion, fostering the human resources, and lending/financing the early initiative procedure, analysis, disbursement and monitoring will have implications/positive impact on the business/internal as well as the impact of a great reputation with uncontrolled NPL/NPF.